Molecular Variation of the Phytopathogenic Fungus Sporisorium reilianum in Valle del Mezquital, Hidalgo - Sánchez Maya, Hasdra Elena; Mercado-Flores, Yuridia; Téllez-Jurado, Alejandro; Pérez-Camarillo, Juan Pablo; Mejía, Omar; Anducho-Reyes, Miguel Angel (Frontiers in Ecology and Evolution, 2020)
Head smut in maize (Zea mays) is a systemic disease caused by the phytopathogenic fungus Sporisorium reilianum. One of the most severely-affected regions in Mexico is Valle del Mezquital in the state of Hidalgo, a high production zone with irrigated agriculture that produces over 50% of maize supplies in the state. This study was designed to analyze the genetic diversity of this phytopathogen isolated from different zones of Valle del Mezquital using the following molecular markers: ITS, aspartyl protease, β-tubulin and the mitochondrial endonuclease LAGLIDADG. Our objective was to estimate the level of genetic variability in a regional space and understand the evolutionary processes to which non-model organisms are subjected. A total of 53 strains of S. reilianum were isolated from the sampling sites and then purified. A Bayesian Analysis of Population Structure (BAPS) analysis of the genetic structuring allowed us to recover three genetic groupings (K = 3), while molecular variance analysis showed a very low fixation index (FST = 0.0146), which was not statistically significant and indicated little between-group genetic differentiation. Also, the value determined for the coefficient of genetic differentiation (Gst) showed little variation among the genetic groups, while the gene flow number (Nm) was 8.25. The Tajima´s D estimator and haplotype network recently indicated a rapid population expansion. Together, these results suggest that reproduction and migration are key factors in the evolution and virulence of this fungus.